2022
DOI: 10.3390/su14127470
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring of Desertification in Ningdong Based on Landsat Images and Machine Learning

Abstract: The ecological stability of mining areas in Northwest China has been threatened by desertification for a long time. Remote sensing information combined with machine learning algorithms can effectively monitor and evaluate desertification. However, due to the fact that the geological environment of a mining area is easily affected by factors such as resource exploitation, it is challenging to accurately grasp the development process of desertification in a mining area. In order to better play the role of remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…The results showed that the accuracy of both the random forest model and the CART with the combination of the four indicators was good, but the accuracy of the random forest was somewhat higher. Li et al [114] applied eleven algorithms: multinomial logistic regression (MLR), linear discriminant analysis (LDA), quadratic discriminant analysis (QDA), CART, support vector machines (SVM), Naive Bayes classifier (NB), K-nearest neighbor (KNN), RF, extremely randomized trees (ERT), AdaBoost (AB), and gradient boosting machine (GBM). The change in desertification in the Ningdong region since 2000 was analyzed.…”
Section: Classical Methods Of Algorithmsmentioning
confidence: 99%
“…The results showed that the accuracy of both the random forest model and the CART with the combination of the four indicators was good, but the accuracy of the random forest was somewhat higher. Li et al [114] applied eleven algorithms: multinomial logistic regression (MLR), linear discriminant analysis (LDA), quadratic discriminant analysis (QDA), CART, support vector machines (SVM), Naive Bayes classifier (NB), K-nearest neighbor (KNN), RF, extremely randomized trees (ERT), AdaBoost (AB), and gradient boosting machine (GBM). The change in desertification in the Ningdong region since 2000 was analyzed.…”
Section: Classical Methods Of Algorithmsmentioning
confidence: 99%
“…However, because of its high stability and its ability to perform efficient processing of large-scale data 64 , the random forest classifier is a more practical integrated learning method, and it can effectively reduce the error of a single classifier and improve the classification accuracy using multiple classifiers for voting classification. Random forest algorithms have randomness in sample and feature selection, which makes it difficult for random forest to fall into overfitting and gives it a good antinoise ability 65 , 66 . In this study, a bagging integrated random forest classification algorithm was used to predict the degree of karst rocky desertification.…”
Section: Methodsmentioning
confidence: 99%
“…RFR uses bagging or bootstrap aggregation techniques in which the aggregated decision tree runs in parallel without interacting. RFR algorithms take advantage of the randomness of sample and feature selection to prevent overfitting and to limit noise [48,49]. However, RFR cannot extrapolate the linear trend to predict new examples with a value beyond those seen in the training data.…”
Section: Machine-learning Models Random Forest Regressionmentioning
confidence: 99%